Tullio Terni (1888–1946): The "column" of spinal cardiovascular regulation. Issue 5 (7th August 2012) - Macchi, V.; Porzionato, A.; Stecco, C.; De, R.
<x xml:space="preserve">Abstract</x> Tullio Terni (1888–1946) was a brilliant anatomist in the School of Medicine of Padova, Italy. He was a versatile scientist who gave fundamental and pioneering contributions in descriptive and experimental cytology, human and comparative morphogenesis, neuroanatomy, embryology and teratology, and regenerative biology. His most famous discovery, which bears his name, is the so‐called "Terni's column." In embryos of chickens, he described the existence in the thoracolumbar region of the spinal cord of a preganglionic nervous center, constituting a longitudinal column of nervous cells between the first thoracic and the second lumbar segments. Tullio Terni embodied the ideal of free science without geographic boundaries. He used cutting‐edge tools, demonstrating his very current approach. Terni studied the organization of tissues and organs and the spatial arrangement and the physical state of the tissues of living systems. He also practiced experimental embryology, which formed the basis of modern techniques in organ transplantation. Moreover, he studied multiple species in order to compare multiple organisms. Terni was a multifaceted scientist. Clin. Anat. 26:544–546, 2013. © 2012 Wiley Periodicals, Inc.